Zum Spannungsverhältnis von Zuwanderung und Sozialstaat - Fischer, Andrea (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1994)
The current debate in Germany about migration and the welfare state focuses on the threat of mass-migration to the maintenance of social security. Not only is the danger of a mass-influx of people exaggerated, moreover there is no empirical evidence for a negative impact of migration on the welfare state in general. With reference to the impossibility of defining a quantitative limit of the capacity to include imigrants the author emphasises the political dimension of the discourse on migration. In discussing different concepts of inclusion the articel raises questions of defining and going beyond the borders of the welfare state.